Stability Study of 0.5 g/mL Urea Oral Solution in InOrpha® - Bourbon Johan; Dory Anne; Perello Laurent; Belotti Laure; Reisz Fanny; Ubeaud-Sequier Genevieve; Gourieux Bénédicte (De Gruyter, 2019)
Urea is recommended in the 2nd line treatment in moderate to severe hyponatraemia induced by syndrome of inappropriate antidiuretic hormone secretion (SIADH), when water restriction is insufficient. A posology of 0.25-0.5 g/kg daily is suggested. A usual but inadequate urea oral preparation, i. e. 10 g urea powder dissolved in 100 mL water before use, was classically compounded. Therefore the pharmacy has developed a 0.5 g/mL urea oral liquid solution in InOrpha® with better organoleptic characteristics to improve treatment adherence and reduce the preparation time. The aim of this study was to determine physicochemical and microbiological stability of the urea oral liquid solution in order to establish a shelf life of the preparation.